2020
DOI: 10.1126/science.aba9287
|View full text |Cite
|
Sign up to set email alerts
|

Predicting temperature mortality and selection in natural Drosophila populations

Abstract: Average and extreme temperatures will increase in the near future, but how such shifts will affect mortality in natural populations is still unclear. We used a dynamic model to predict mortality under variable temperatures on the basis of heat tolerance laboratory measurements. Theoretical lethal temperatures for 11 Drosophila species under different warming conditions were virtually indistinguishable from empirical results. For Drosophila in the field, daily mortality predicted from ambient temperature record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
159
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(170 citation statements)
references
References 31 publications
6
159
0
Order By: Relevance
“…The proper ramping rate to measure CT max should be designed on the basis of taxon-group (Kovacevic, Latombe & Chown, 2019). Although the present ant studies and Drosophila studies present similar correlation between CT max and ramping rate in the static and dynamic assays (Jørgensen, Malte & Overgaard, 2019; Rezende et al , 2020), we found that CT max measurements through the “best” ramping rate can be a reliable predictor for ant foraging activity and associated maximum temperatures measured in the field. This comparison suggests that ramping rate used in CT max measurements should also be tested against species upper thermal limit measured in the field (e.g.…”
Section: Resultssupporting
confidence: 61%
“…The proper ramping rate to measure CT max should be designed on the basis of taxon-group (Kovacevic, Latombe & Chown, 2019). Although the present ant studies and Drosophila studies present similar correlation between CT max and ramping rate in the static and dynamic assays (Jørgensen, Malte & Overgaard, 2019; Rezende et al , 2020), we found that CT max measurements through the “best” ramping rate can be a reliable predictor for ant foraging activity and associated maximum temperatures measured in the field. This comparison suggests that ramping rate used in CT max measurements should also be tested against species upper thermal limit measured in the field (e.g.…”
Section: Resultssupporting
confidence: 61%
“…Modelling and discussion of TTL predictions beyond the boundaries of the input data has recently gained traction (see examples in Rezende et al 44 and Buckley 45 ) but we caution that the potent exponential nature of the TTL requires careful consideration as it is both easy and enticing to misuse this model.…”
Section: Practical Considerations and Pitfalls For Model Interpretationmentioning
confidence: 99%
“…Previously, it has been shown that Drosophila struggle to survive on corresponding experimental diets at high temperatures (1) and that wild flies seek yeast-based food in the summer (3). Although global warming is the main problem our society is facing in this 21st century, its consequence on the animal kingdom is not understood (8,9). In this paper, we provide new insights in the dual response of one neuronal subset to diet and changes of environmental temperatures.…”
Section: Introductionmentioning
confidence: 99%